Jewish, Christian, and Marrano Messianism in Iberia in the Turn of the Fifteenth Century: Common Atmosphere and Symbiotic Relationships - Gross, Avraham (MiKAN, 2007)
Messianism has been long recognized as a powerful motif in the history of the Jews of Spain prior to the Expulsion (1492) and in the following generations. Hopes for redemption and return to Judaism were also central to the life of the Marranos. However, the study of messianic thought, expectation and awakening did not consider Christian messianism in Spain during this period. This article attempts to show that Jewish and Marranic messianism cannot be fully understood outside of the context of parallel Iberian-Christian hopes. Three issues are examined in order to illustrate the main thesis: Columbus' messianic thought and aspirations; a Jewish visionary from Spain who was arrested by the king of Portugal and wrote about his visions and experiences in Portugal in 1497; and the “Prophecies of the Child” [Nevo'ut Ha-Yeled], All three, it is claimed, can only be properly understood against the backdrop of the Iberian-Christian messianism that flourished in the second half of the fifteenth century.